Review article: implementation of a diet low in FODMAPs for patients with irritable bowel syndrome—directions for future research. Issue 2 (27th December 2018) - Mitchell, Hannah; Porter, Judi; Gibson, Peter R.; Barrett, Jacqueline; Garg, Mayur
Summary: Background: Despite the efficacy of a diet low in fermentable oligosaccharides, disaccharides, monosaccharides, and polyols (FODMAP) for patients with irritable bowel syndrome, many questions remain unanswered with respect to its clinical implementation. Aim: To review literature to identify, synthesise, and provide direction for future research in the implementation and evaluation of the low FODMAP diet. Methods: Bibliographical searches were performed in Ovid Medline, CINAHL, Scopus and PubMed from database commencement until September 2018, with search terms focused on the population (irritable bowel syndrome) and intervention of interest (FODMAP). Results: Predictors of response to a low FODMAP diet remain under investigation, with preliminary data supporting faecal microbiota or faecal volatile organic compound profiling. Training of clinicians, and standards for the education of patients about the phases of a low FODMAP diet, as well as the role of Apps, require formal evaluation. There are limited data on the longer term efficacy and safety of the low FODMAP diet with respect to sustained symptom control, effect on quality of life and healthcare utilisation, nutritional adequacy, precipitation of disordered eating behaviours, effects on faecal microbiota and metabolomic markers, and subsequent translation to clinical effects. Conclusions: Many gaps in implementation of the low FODMAP diet in clinical practice, as well as long‐term safety and efficacy, remain for further investigation.